ANALISIS WACANA KRITIS PADA TEKS BERITA PROGRAM MAKAN BERGIZI GRATIS DI MEDIA ONLINE KOMPAS.COM DAN HARIAN SIB.COM - Sinaga, Devira Ekklesia; Tambunan, Marlina Agkris; Silitonga, Immanuel Doclas Belmondo; Siregar , Junifer; Saragih, Vita Riahni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the construction of news coverage on the Free Nutritious Meal (MBG) program in Kompas.com and HarianSIB.com using Teun A. van Dijk’s Critical Discourse Analysis model, which includes the dimensions of text structure, social cognition, and social context. This research employs a descriptive qualitative method with data in the form of news texts published between 2025–2026 and in-depth interviews with journalists. The findings show that, at the textual level, both media construct discourse through macrostructure, superstructure, and microstructure, but with different emphases. Kompas.com tends to highlight institutional clarification, administrative aspects, and government perspectives, while HarianSIB.com emphasizes the impact of events, such as poisoning cases and victims’ conditions. At the level of social cognition, journalists in both media adhere to verification and journalistic ethics; however, Kompas.com relies more on official sources, whereas HarianSIB.com is more influenced by field conditions. In the social context dimension, news discourse is dominated by institutional actors who have power and access in shaping meaning. This study reveals that the media not only convey information but also actively construct reality through different framing strategies, which in turn influence public perceptions of the MBG program.